1998
DOI: 10.1159/000020836
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Anomalies in Abnormal Human Pregnancies

Abstract: Objective: The aim of this study was to describe the cytogenetic observations on abnormal human pregnancies (anembryonic pregnancy, early fetal loss, and hydatidiform moles), and to detect the most frequent or typical chromosomal aberration for anembryonic pregnancy and early fetal loss. Study Design: Abnormal pregnancies were divided into three clinical and morphological groups: (a) anembryonic pregnancy; (b) early fetal loss, and (c) hydatidiform mole. Of the 119 karyotyped tissue samples, 42 (35%) were from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 17 publications
0
10
1
Order By: Relevance
“…These results are at variance with previous reports by other authors showing no association between morphological features and karyotypes in EPL14–16, 26. However, the total percentage and distribution of the different chromosomal abnormalities as well as the male to female sex ratio found in the present study did not differ significantly from those reported in previous cytogenetic studies performed on EPLs20–22, 24, 25, adding strength to our results.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…These results are at variance with previous reports by other authors showing no association between morphological features and karyotypes in EPL14–16, 26. However, the total percentage and distribution of the different chromosomal abnormalities as well as the male to female sex ratio found in the present study did not differ significantly from those reported in previous cytogenetic studies performed on EPLs20–22, 24, 25, adding strength to our results.…”
Section: Discussioncontrasting
confidence: 78%
“…However, few of these studies investigated the relationship between chromosomal abnormalities and TVS findings in EPL. Moreover, only a few ultrasound findings were taken into account, such as the presence or absence of an embryonic pole, variations from the expected crown–rump length (CRL) of the embryo‐fetus, presence of trophoblastic disease or empty sac 23–25.…”
Section: Introductionmentioning
confidence: 99%
“…From the 13 included studies, 2 × 2 tables for the chromosomal abnormality rate in EPL with or without ultrasound identifiable embryo could be constructed6, 7, 10, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21; four of these studies were included for the chromosomal abnormality rate in EPL with short CRL7, 10, 14, 20; two studies for the chromosomal abnormality rate in EPL with small GS7, 10; two studies for the chromosomal abnormality rate in EPL with YS only7, 17; two studies for the chromosomal abnormality rate in EPL with symmetrical arrested growth7, 10; one study for the chromosomal abnormality rate in EPL with enlarged YS 10 Table 1 summarized the general information of the 13 included studies in the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Two distinct phenotypes are known to be associated with triploidy. A minority of foetuses presents with moderate growth retardation, proportionately sized body parts and particularly large placentas with partial hydatidiform mole (type I [4][5][6] ).…”
Section: Introductionmentioning
confidence: 99%